2016
DOI: 10.1080/03079457.2016.1248898
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity, tissue distribution, shedding and environmental detection of two strains of IBDV following infection of chickens at 0 and 14 days of age

Abstract: Infectious bursal disease virus (IBDV) is endemic to most poultry-producing countries worldwide. Immunosuppressive classical and variant IBDV strains endemic to Australia are genetically distinct from other international strains. We report the results of infection experiments with Australian classical strain 06/95 and variant strain 02/95 in SPF chickens. We tested the effects of strain and age of infection on bursal atrophy, viral RNA (vRNA) load in bursa of Fabricius (bursa), spleen, thymus, caecal tonsils, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
(49 reference statements)
5
18
1
Order By: Relevance
“…Bursal damage, measured by the bursa:body weight ratio, was more noticeable and precocious after ITA-IBDV inoculation. This feature has previously been described for 'variant' IBDV, which has been reported to cause earlier and more severe bursal atrophy than 'classical' strains (Hassan, Al-Natour, Ward, & Saif, 1996;Jayasundara et al, 2017;Sharma et al, 1989).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Bursal damage, measured by the bursa:body weight ratio, was more noticeable and precocious after ITA-IBDV inoculation. This feature has previously been described for 'variant' IBDV, which has been reported to cause earlier and more severe bursal atrophy than 'classical' strains (Hassan, Al-Natour, Ward, & Saif, 1996;Jayasundara et al, 2017;Sharma et al, 1989).…”
Section: Discussionsupporting
confidence: 66%
“…Bursal damage, measured by the bursa:body weight ratio, was more noticeable and precocious after ITA‐IBDV inoculation. This feature has previously been described for ‘variant’ IBDV, which has been reported to cause earlier and more severe bursal atrophy than ‘classical’ strains (Hassan, Al‐Natour, Ward, & Saif, ; Jayasundara et al, ; Sharma et al, ). The histopathology scores of the bursa confirmed the aggressiveness of the ITA‐IBDV strain tested in this organ, with scores indicating severe lymphoid depletion, as previously reported by Sharma et al () for the American ‘variant’ strain.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…These strains are endemic and genetically distinct from overseas classical, variant and vvIBDV strains . In vivo studies have confirmed the immunosuppressive effects of infection with the Australian classical and variant strains …”
mentioning
confidence: 88%